Challenges in textile wastewater and current palliative methods: An overview - Bello, Ibrahim Adebayo; Kabbashi, Nassereldeen Ahmed; Alam, Md. Zahangir; Al-Khatib, Ma'an Fahmi Rashid; Murad, Fatin Nabilah; Qudsieh, Issam Yassin (International Islamic University Malaysia, 2017)
Effluents from dye and textile industries are highly contaminated and toxic to the environment. High concentrations of non-biodegradable compounds contribute to increases in biochemical oxygen demand (BOD) and chemical oxygen demand (COD) of the wastewater bodies. Dyes found in wastewater from textile industries are carcinogenic, mutagenic, or teratogenic. Biological processes involving certain bacteria, fungi, activated carbon, and carbon nanotubes (CNTs) are promising methods for treating the wastewater. These methods are either inefficient or ineffective. These complexities necessitate a search for new approaches that will offset all the shortcomings of the present solutions to the challenges faced by textile wastewater management. This article reviews the past and recent methods used in the treatment of textile dye wastewater and future opportunities for efficient treatment of textile wastewater.